Penerapan Metode MOORA dan ROC Dalam Penerimaan Siswa Baru - Fredi Nandus Gea; Rupa Bertha L Pakpahan (TIN: Terapan Informatika Nusantara, 2023)
Acceptance of new students is part of the administrative process of admitting new students to the next educational level. This procedure is usually carried out every year. SMP A is a junior high school that always applies the procedure for admitting new students every year. The problem with admitting new students is the high number of students enrolled, making it difficult for the committee to select prospective students who are eligible and who are not eligible to enroll in SMP A. It is necessary to use a decision support system to solve various unstructured and semi-structured problems. This study aims to design a decision support system for implementing new student admissions using the Moora and Roc method for making decisions in new student admissions. After calculating the best alternative, it was found that Darma Situmorang was ranked first with a Yi value of 0.4565, while Dian Yunita Nababan with alternative A3 was ranked second with a Yi value of 0.4417. In the decision-making process, there are several methods to choose from, but in this study, the MOORA method was chosen because of its ability to better compare the criteria of each different alternative